The serodominant secreted effector protein of Salmonella, SseB, is a strong CD4 antigen containing an immunodominant epitope presented by diverse HLA class II alleles. Issue 3 (November 2014) - Reynolds, Catherine J.; Jones, Claire; Blohmke, Christoph J.; Darton, Thomas C.; Goudet, Amelie; Sergeant, Ruhena; Maillere, Bernard; Pollard, Andrew J.; Altmann, Daniel M.; Boyton, Rosemary J.
Summary Detailed characterization of the protective T‐cell response in salmonellosis is a pressing unmet need in light of the global burden of human Salmonella infections and the likely contribution of CD4 T cells to immunity against this intracellular infection. In previous studies screening patient sera against antigen arrays, SseB was noteworthy as a serodominant target of adaptive immunity, inducing significantly raised antibody responses in HIV‐seronegative compared with seropositive patients. SseB is a secreted protein, part of the Espa superfamily, localized to the bacterial surface and forming part of the translocon of the type III secretion system (T3SS) encoded by Salmonella pathogenicity island 2. We demonstrate here that SseB is also a target of CD4 T‐cell immunity, generating a substantial response after experimental infection in human volunteers, with around 0·1% of the peripheral repertoire responding to it. HLA‐DR/peptide binding studies indicate that this protein encompasses a number of peptides with ability to bind to several different HLA‐DR alleles. Of these, peptide 11 (p11) was shown in priming of both HLA‐DR1 and HLA‐DR4 transgenic mice to contain an immunodominant CD4 epitope. Analysis of responses in human donors showed immunity focused on p11 and another epitope in peptide 2. The high frequency of SseB‐reactive CD4 T cells and the broad applicability to diverse HLA genotypes coupled with previous observations of serodominance and protective vaccination in mouse challenge experiments, make SseB a plausible candidate for next‐generation Salmonella vaccines.